Professional Training of Nurses with Social Commitment in Elderly Care: the influence of the socio-educational environment (Research, Society and Development, 2020)
The objective of the study was to understand the training of nurses for professional practice with social commitment in consultation with the elderly, considering the socio-educational environment. Pierre Bourdieu's theoretical framework was used. The methodology was a qualitative documentary analysis of the pedagogical project of the Aurora de Afonso Costa Nursing School, which is published on the institution's website, in light of the content analysis. Content analysis was used and from it three categories were found: knowledge / knowledge and those of everyday nursing praxis are seen from the perspective of integration between theory and practice; “Social commitment” refers to having a professional attitude towards the individual, the family, and the community in valuing life and reveals that social commitment is related to training and social participation, within the concept of practice between subjects and mediator of care in the socio-educational environment. Understanding the professional training of nurses with social commitment in the socio-educational environment organizes consultation with the elderly with knowledge for the academic community.